Use of {99m}Tc-HMPAO for Scintigraphic Evaluation of Cerebral Microcirculation in the Patients with Persistent Atrial Fibrillation; Advanced Materials Research : Radiation and nuclear techniques in material science; Vol. 1084 : Physical-Technical Problems of Nuclear Science, Energy Generation, and Power Industry (PTPAI -2014) - Efimova N. Yu. Nataliya Yurievna; Chernov V. I. Vladimir Ivanovich; Efimova I. Y.; Popov S. V. (Radiation Technologies in Medicine, 2015)
Title screen